A novel methodology for measurement of the intradiscal pressure and height disc variation of intervertebral disc under compression - Araújo, Ângelo Rafael Gomes (2013)
The intervertebral disc (IVD) is subjected to several types of loading during daily routine events. However, the overloading on this structure induces higher intradiscal pressure (IDP), which could cause severe damage on its structure. This study describes a new approach to monitor IDP and determine the height disc variation by applying external pressure, while a motion segment (assembly composed by vertebra-disc-vertebra) compressed at a physiological load. This methodology includes the use of a pneumatic structure that applies a certain pressure on the hydrostatic system, forcing a fluid to enter into the motion segment, through a screw with a drilled hollow along its entire length with an internal bore. Preliminary results indicates these methodology presents high potential to efficiently pressurize the IVD, providing a useful tool to better understand the response of this structure under pressure.